Hubungan Status Gizi dengan Tingkat Kebugaran Berdasarkan 6 Minute Walk Test - M. Azhari Hakim; Rizky Suganda Prawiradilaga; Sadiah Achmad (UNISBA Press, 2024)
Abstract. Physical fitness is a person's ability to carry out their daily activities efficiently without producing significant fatigue. Physical fitness is important for medical students to carry out their daily activities that have a busy schedule. This study aims to determine the relationship between nutritional status with fitness level. This study used observational analytic quantitative research with a cross-sectional design. The subjects in this study were active students of the Faculty of Medicine, Islamic University of Bandung in the academic year 2022-2023 as many as 87 people aged 20 to 29 years. Nutritional status data were obtained from anthropometric measurements in the form of body mass indeks and measuring fitness levels using the six minute walk test. Statistical tests used the Spearman correlation test. The results showed that there was a statistically significant relationship between body mass index and fitness level (p=0.013). This result may be due to many other factors that can affect fitness levels such as adequate rest, smoking status, health status, and so on. Abstrak. Kebugaran jasmani ialah kemampuan seseorang dalam melaksanakan aktivitas hariannya dengan efisien tanpa menghasilkan kelelahan yang berarti. Kebugaran jasmani penting bagi mahasiswa kedokteran untuk menjalankan aktivitas hariannya yang memiliki jadwal yang padat. Penelitian ini bertujuan untuk mengetahui hubungan status gizi dengan tingkat kebugaran. Penelitian ini menggunakan jenis penelitian kuantitatif analitik observasional dengan desain cross-sectional. Subjek pada penelitian ini mahasiswa aktif Fakultas Kedokteran Universitas Islam Bandung tahun ajaran 2022-2023 sebanyak 87 orang berusia 20 sampai 29 tahun. Data status gizi diperoleh dari pengukuran antropometri berupa indeks massa tubuh dan pengukuran tingkat kebugaran menggunakan six minute walk test. Uji statistik menggunakan uji spearman correlation. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan secara statistik antara indeks massa tubuh dengan tingkat kebugaran (p=0.013). Hasil ini dapat disebabkan karena banyak faktor lain yang dapat mempengaruhi tingkat kebugaran seperti kecukupan istirahat, status merokok, status kesehatan, dan sebagainya.